2021
DOI: 10.3390/antiox10111680
|View full text |Cite
|
Sign up to set email alerts
|

Over-Expression of Chorismate Mutase Enhances the Accumulation of Salicylic Acid, Lignin, and Antioxidants in Response to the White-Backed Planthopper in Rice Plants

Abstract: The white-backed planthopper (WBPH) is a serious pest of rice crop and causes sever yield loss each year, especially in Asian countries. In this study, we used chorismate mutase (CM) transgenic line to examine the defense mechanism of rice plants against WBPH. The survival rate of WBPHs, infestation rate of plants, lignin biosynthesis, transcriptional regulation of related genes, salicylic acid (SA) accumulation and signaling and antioxidants regulation were investigated. The WBPH population decreased by 67% i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 46 publications
0
18
0
Order By: Relevance
“…Many studies have reported that lignin, acting as the first physical barrier, can withstand the expending of pathogens [ 32 , 37 , 38 , 39 ]. There is also a report on the co-regulation of pathogenic bacteria resistance with SA [ 59 ]. Our results are consistent with these studies and further confirm that lignin may act as the first physical line of defense against SMV, then SA can activate several plant defense responses, which together constrain either or both the amplification and intercellular movement of SMV.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have reported that lignin, acting as the first physical barrier, can withstand the expending of pathogens [ 32 , 37 , 38 , 39 ]. There is also a report on the co-regulation of pathogenic bacteria resistance with SA [ 59 ]. Our results are consistent with these studies and further confirm that lignin may act as the first physical line of defense against SMV, then SA can activate several plant defense responses, which together constrain either or both the amplification and intercellular movement of SMV.…”
Section: Discussionmentioning
confidence: 99%
“…Histochemical staining with DAB and trypan indicates that H 2 O 2 accumulation was reduced in GA-treated plants and a lower amount of cell death was visualized in GA-treated plants. Previous studies suggested that high H 2 O 2 accumulation and cell death were seen in WBPH-infested plants [ 7 ]. Our study suggests that giving exogenous GA treatment to WBPH-infested plants can reduce these effects, which is in line with previous reports that applying exogenous GA can reduce the intracellular ROS under stress conditions [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…The water was changed daily. After three days of soaking, the pre-germinated seeds were transferred to soil and kept in the dark for three days until successful growth was observed, as published previously [ 7 ], and the seedlings were kept in the greenhouse for further experimentation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Approximately 25% of global rice production is lost annually due to damage caused by pest assaults [ 4 ]. The white-backed planthopper (WBPH) is a serious insect pest that damages plants through cellsap-sucking and viral transmissions, and causes severe losses in yield each year, especially in Asian countries [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%